Reason and Revelation in Islamic Epistemology: A Hierarchical–Integrative Reconstruction - Makrifat Makrifat; Indo Santalia; Andi Aderus; Yessy Kurniati (STIT Sunan Giri Bima, 2026)
This article examines the epistemological relationship between human reason (ʿaql) and revelation in Islamic thought, addressing the ongoing tension between rational autonomy and textual authority in contemporary interpretations. While existing studies often treat reason and revelation in isolation or as competing sources of knowledge, this study seeks to clarify how classical Islamic intellectual traditions conceptualize their relationship in an integrated and systematic manner. The study aims to analyze how major disciplines—particularly kalām (theology), uṣūl al-fiqh (legal theory), Qur’anic exegesis (tafsīr), and Islamic philosophy (falsafah)—define the function, scope, and limits of reason in relation to revelation. To achieve this, the research employs a qualitative library-based method, drawing on primary classical texts and supported by contemporary scholarly literature. The findings demonstrate that reason is consistently regarded as an essential epistemic instrument that enables moral responsibility, interpretive reasoning, and doctrinal articulation. However, its operation is normatively bounded, especially in matters related to metaphysics, the unseen, and definitive (qaṭʿī) texts. This study contributes to the field of Islamic epistemology by proposing a hierarchical–integrative model in which reason functions as a necessary yet subordinate instrument under the normative authority of revelation.